The val66met polymorphism of brain‐derived neurotrophic factor is associated with human esophageal hypersensitivity. Issue 2 (1st October 2012) - Vasant, D. H.; Payton, A.; Mistry, S.; Thompson, D. G.; Hamdy, S.
Abstract Background Recent evidence implicates brain‐derived neurotrophic factor (BDNF) in visceral hypersensitivity and pain in functional gastrointestinal disorders. We hypothesized that presence of the val66met polymorphism in the BDNF gene would be linked to increased esophageal sensitivity to electrical stimulation. Methods A total of 39 healthy volunteers (20 males, mean age 30) compliant with inclusion criteria after screening procedures were genotyped for BDNF polymorphisms and completed an Hospital Anxiety and Depression Scale (HADS) questionnaire. Sensory (ST) and pain (PT) thresholds in the proximal (PE) and distal (DE) esophagus were determined using electrical stimuli to a swallowed intraluminal catheter with bipolar electrodes by an investigator blinded to the subjects' genotype. For comparison, somatic ST and PT (hand and foot) were also tested. HADS scores together with esophageal and somatic thresholds were then correlated with BDNF polymorphism status. Key Results Eleven of 39 (28%) volunteers had at least one Met allele (Met carriers). When compared with Val/Val, Met carriers had lower esophageal PT (Median PT [mA]: Val/Val vs Met carriers, PE; 49.4 vs 44.3, P = 0.033, DE: 63.8 vs 55.4, P = 0.045) with higher proportion of Val/Val subjects in the upper quartile for PT in both PE (P = 0.021) and DE (P = 0.033), yet similar somatic PT (Median PT [mA] Hand; 33.6 vs 38.0, P = 0.22, Foot; 44.7 vs 44.0, P = 0.48). Sensitivity results were independent of anxiety (P = 0.66) and depression (P = 0.33) scores. Conclusions & Inferences val66met BDNF polymorphisms are associated with increased esophageal sensitivity to experimental electrical stimulation. Thus, BDNF genotype may be a useful biomarker for electrical sensitivity in the healthy human esophagus.